Helicons in plasma solid-state waveguide of cylindrical configuration - Averkov, Yu.O.; Prokopenko, Yu.V.; Yakovenko, V.M. (Вопросы атомной науки и техники, 2019)
The theory of electromagnetic eigenwaves of a cylindrical plasma waveguide located in a constant longitudinal magnetic field has been created. A dispersion equation has been obtained under condition when the ratio of the collision frequency of the majority charge carriers to their cyclotron frequency is substantially less than one. It is shown there are bulk-surface helicons in a plasma waveguide. In the absence of charge-carrier collisions, their propagation is accompanied by a surface current directed parallel to the longitudinal axis of symmetry of the cylinder. Collisions of charged particles destroy the surface current and lead to the formation of additional H-type hybrid waves, the field localizations of which are concentrated near the side surface of the waveguide. The nonreciprocity effect of the eigenwaves, differing in the direction of propagation along the azimuthal coordinate, as well as when the direction of the external magnetic field is changed, has been discovered. Побудовано теорію власних електромагнітних хвиль циліндричного плазмового хвилеводу, який розташовано в постійному поздовжньому магнітному полі. Отримано дисперсійне рівняння в умовах, коли відношення частоти зіткнень основних носіїв заряду до їх циклотронної частоти багато менше одиниці. Показано, що в плазмовому хвилеводі існують об'ємно-поверхневі гелікони. Їх поширення у відсутності зіткнень носіїв заряду супроводжується поверхневим струмом, який спрямований паралельно поздовжній осі симетрії циліндра. Зіткнення заряджених частинок руйнують поверхневий струм і призводять до утворення додаткових гібридних хвиль H-типу, локалізації полів яких зосереджені поблизу бокової поверхні хвилеводу. Виявлено ефект невзаємності власних хвиль, що відрізняються напрямком поширення за азимутальною координатою, а також при зміні напрямку зовнішнього магнітного поля. Построена теория собственных электромагнитных волн цилиндрического плазменного волновода, расположенного в постоянном продольном магнитном поле. Получено дисперсионное уравнение в условиях, когда отношение частоты столкновений основных носителей заряда к их циклотронной частоте много меньше единицы. Показано, что в плазменном волноводе существуют объёмно-поверхностные геликоны. Их распространение в отсутствие столкновений носителей заряда сопровождается поверхностным током, направленным параллельно продольной оси симметрии цилиндра. Столкновения заряженных частиц разрушают поверхностный ток и приводят к образованию дополнительных гибридных волн H-типа, локализации полей которых сосредоточены вблизи боковой поверхности волновода. Обнаружен эффект невзаимности собственных волн, отличающихся направлением распространения по азимутальной координате, а также при изменении направления внешнего магнитного поля.